BRIDGING THE GAP: REFLECTIONS ON EAP MATERIALS AT PHARMACY ACADEMY OF SURABAYA - Lusiyani, Ria; Wahyunianto, Dian (Universitas Muhammadiyah Semarang, 2019)
This study aims to evaluate the course module used in EAP teaching at Pharmacy Academy of Surabaya. The coursebook was evaluated in terms of its subject matter, structure and capability to meet students‘ need. Two instruments were employed to draw potential strengths and weaknesses of the coursebook. Firstly, an evaluation checklist adapted from several literatures was designed to serve teachers’ perspective about the coursebook. Secondly, a set of questions was constructed to observe students‘ feedback. Surprisingly, the result of the study shows that eight chapters presented in the module are, considerably, more appropriate for EGAP class rather than ESAP class. Besides, it was found that each chapter is less-defined as every of them is organized differently. Furthermore, the whole aspects conclude that a lot of room remains for improvement for the materials in order to meet the students‘ need.